Transcend the Death of Child with Cancer: Professional Health Experiences - Paula Vega Vega; Paola Carrasco Aldunate; Leticia Rojo Suárez; María Eugenia López Encina; Rina González Rodríguez; Ximena González Briones (Universidad Católica del Uruguay, 2021)
Objective: To reveal the perception of grief support of professionals in pediatric oncology units, after the death of the patients. Method: Qualitative phenomenological study. 22 in-depth interviews were conducted with professionals from 5 pediatric oncology units of public hospitals in Santiago. Once the narratives were transcribed, the comprehensive analysis and subsequent triangulation of the data was performed, achieving saturation. Results: Professionals perceive themselves supported in their grief by being able to experience the losses in a protected environment and feeling supported by their surroundings. They recognized the existence of external and internal factors that facilitated the process of grief. However, this support is perceived as insufficient, as there is a lack of formal support from the institution, as well as a protected grief period, or support from mental health professionals to the teams. All death experiences allow professionals to transcend their pain based on lifelong learning and to give meaning to their work. Conclusion: Grief support felt by the professionals is generated from their own initiatives of re-encounter within the teams, which is insufficient. Therefore, training in coping with death is necessary from undergraduate level, which would allow greater cohesiveness in coping and greater self-care within the teams.